Level of knowledge of tuberculosis among high school students from Lima, Peru, 2019 - Norabuena Granda, Marina Alejandra (2020)
Objective: To determine the level of knowledge of tuberculosis among fourth- and fifth-year high school students from the education center No. 2027 “José María Arguedas". Materials and methods: A quantitative, descriptive, prospective and cross-sectional study. The sample consisted of 146 fourth- and fifth-year high school students enrolled during 2019. The research instrument was a questionnaire modified and validated by experts using a Kappa coefficient of 1.01. The reliability was found to be 0.70, according to the KuderRichardson coefficient distributed into two dimensions, which evaluated the students’ level of knowledge of tuberculosis. Results: The average age of the participants was 15.39 ± 0.85 years, with a median age of 15 years. Ages ranged from 14 to 18 years. In general terms, the participants showed a medium level of knowledge of tuberculosis (50 %). Concerning the dimensions, they showed a medium level of knowledge for both the disease dimension (54.1 %) and the prevention dimension (43.8 %). Conclusions: Fifty percent (50 %) of the students have a medium level of knowledge of tuberculosis, despite having received information at some point during their school years. This demonstrates the need to monitor the education center.